2017
DOI: 10.1111/jcpe.12783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA methylation of inflammatory genes following treatment of chronic periodontitis: A pilot case–control study

Abstract: Periodontal therapy resets the DNA methylation status of inflammatory gene for COX-2 in patients with periodontal disease. DNA methylation levels of TNF-α, IFN-γ and LINE-1 were sustained in periodontitis sites despite therapy. Future studies should consider an expanded panel of inflammatory genes over time. (ClinicalTrials.gov NCT02835898).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
(78 reference statements)
0
30
0
Order By: Relevance
“…This is not surprising, as the expression of pro-inflammatory cytokines, and other inflammatory-related genes may be modulated by epigenetic mechanisms. [48][49][50] Furthermore, chronic inflammation triggered by various factors can induce aberrant DNA methylation, which in some cases may initiate cancer-specific epigenetic changes in epithelial cells. [51][52][53] In humans, an overlap between the DNA methylation pattern of chronic periodontitis and oral SCC has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as the expression of pro-inflammatory cytokines, and other inflammatory-related genes may be modulated by epigenetic mechanisms. [48][49][50] Furthermore, chronic inflammation triggered by various factors can induce aberrant DNA methylation, which in some cases may initiate cancer-specific epigenetic changes in epithelial cells. [51][52][53] In humans, an overlap between the DNA methylation pattern of chronic periodontitis and oral SCC has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on DNA methylation in periodontal tissues identified hypomethylation profiles within the IFN‐γ , IL‐6 , and TNF‐α promoters that are associated with increased IFN‐γ, IL‐6, and TNF‐α transcription in gingival biopsies from patients with chronic PD . Interestingly, it was recently reported that periodontal therapy can reduce methylation status of prostaglandin‐endoperoxide synthase 2 (PTGS2) but not IFN‐γ and TNF‐α at healthy and PD sites over time . Despite its limitations in sample size, different sampling sites per time point and relatively short follow‐up, this study suggests that local disease activity influences the epigenetics of the tissues, which may be modulated by environmental factors, including the microbiota.…”
Section: Mac Functions In Inflammation Resolution and Osteoimmunologymentioning
confidence: 95%
“…As such, these epigenetically altered tissues subsequent to tooth extraction may differ from those not exposed to epigenetic cues such as histone deacetylation or DNA hypermethlyation. 23,24 This connection could be the missing link between periodontitis and peri-implantitis and could serve as a rationale for why patients with a history of periodontal disease, even with enhanced oral hygiene measures, should have more intense monitoring. This theory needs to be tested, given the very limited information available on epigenetic mechanisms and the initiation and progression of peri-implantitis.…”
mentioning
confidence: 99%